2010
DOI: 10.1016/j.jinorgbio.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Nitroimidazole conjugates of bis(thiosemicarbazonato)64Cu(II) – Potential combination agents for the PET imaging of hypoxia

Abstract: Combination agents comprising two different pharmacophores with the same biological target have the potential to show additive or synergistic activity. Bis(thiosemicarbazonato)copper(II) complexes (e.g. 64Cu-ATSM) and nitroimidazoles (e.g. 18F-MISO) are classes of tracer used for the delineation of tumor hypoxia by positron emission tomography (PET). Three nitroimidazole-bis(thiosemicarbazonato)copper(II) conjugates were produced in order to investigate their potential as combination hypoxia imaging agents. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
(57 reference statements)
3
25
0
Order By: Relevance
“…After 64 Cu-ATSM was incubated in serum in vitro, 10%-15% of the radioactivity was associated with precipitated protein after 0-2 h and not extracted into ethanol. This was in agreement with the reported results for 64 Cu-ATSM and related 64 Cu-bis(thiosemicarbazones) after incubation with serum, for which typically approximately 20% of activity was protein-bound (24,27,31). Radio-thin-layer chromatography (radio-TLC) and high-performance liquid chromatography confirmed that the ethanolextractable radioactivity contained only intact 64 Cu-ATSM in agreement with previous in vitro findings (24,27), indicating stability of the complex in serum in vitro.…”
Section: Cu Speciation In Vitro and In Vivo In Bloodsupporting
confidence: 92%
“…After 64 Cu-ATSM was incubated in serum in vitro, 10%-15% of the radioactivity was associated with precipitated protein after 0-2 h and not extracted into ethanol. This was in agreement with the reported results for 64 Cu-ATSM and related 64 Cu-bis(thiosemicarbazones) after incubation with serum, for which typically approximately 20% of activity was protein-bound (24,27,31). Radio-thin-layer chromatography (radio-TLC) and high-performance liquid chromatography confirmed that the ethanolextractable radioactivity contained only intact 64 Cu-ATSM in agreement with previous in vitro findings (24,27), indicating stability of the complex in serum in vitro.…”
Section: Cu Speciation In Vitro and In Vivo In Bloodsupporting
confidence: 92%
“…Similar tumour uptakes were observed for 2 and 3, with corresponding values of 2.97 %ID/g and 2.56 %ID/g at 60 min post-injection [33]. The tumour/blood (T/B) and tumour/muscle (T/M) ratios at 60 min for complex 2 were 1.08 and 2.14 while those of complex 3 were 1.17 and 1.87, respectively [33].…”
Section: Copper Bis(thiosemicarbazone) Nitroimidazolessupporting
confidence: 56%
“…In vitro studies showed rapid uptake of this compound by hypoxic cells, reaching a maximum at 5 min and remaining constant for up to 60 min [39]. Related compounds include conjugates derived from the diacetyl-bis(N 4 -methylthiosemicarbazone) (H2ASTM/A) platform linked to 2-or 4-nitroimidazole, and diacetyl-2-(4-N-methyl-3-thiosemicarbazone)-3-(4-N-ethylamino-3-thiosemicarbazone) (H2ASTM/en; 3, Figure 4) [33]. Cyclic voltammograms displayed quasi-reversible reduction waves centred at -0.60 V, which was attributed to the reduction of Cu II to Cu I .…”
Section: Cu and 67mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroimidazoles which show selective accumulation in hypoxic cells are the most widely explored molecules for delineating hypoxic tumor cells from normoxic cells [10]. Several nitroimidazole radiopharmaceuticals based on PET as well as SPECT isotopes are reported [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Presently, [ 18 F]fluoromisonidazole ([ 18 F]FMISO), a 2-nitroimidazole-radiotracer, is the radiopharmaceutical of choice for clinical imaging of tumor hypoxia [29].…”
Section: Introductionmentioning
confidence: 99%